Investigational non-JAK inhibitors for chronic phase myelofibrosis. (3rd May 2020) - Bankar, Aniket; Gupta, Vikas
ABSTRACT: Introduction: Patients with myelofibrosis (MF) have no effective treatment option after the failure of approved JAK inhibitor (JAKi) therapy. Non-JAK inhibitors (non-JAKi) that target non-canonical molecular pathways are undergoing clinical evaluations to optimize efficacy and/or to reduce hematological toxicity of JAKi. Area covered: This article reviews the efficacy data from completed and ongoing early phase clinical trials of non-JAKi agents for chronic phase MF. The article also illuminates some of the challenges of myelofibrosis drug development. Expert opinion: Most non-JAKi agents tested so far have shown modest benefit in improving the efficacy of ruxolitinib. Several novel agents such as BET inhibitor- CPI-0610, activin receptor ligand trap- luspatercept, recombinant pentraxin-PRM-151, telomerase inhibitor- imetelstat and bcl-2 inhibitor- navitoclax, have shown promising activity; however, they require vigorous evaluation in randomized controlled trials to understand the clinical benefit. Drugs that target new molecular pathways (MDM2, p-selectin, TIM-3, TGF-β, aurora kinase) and immune-based strategies (CALR vaccine, anti-PD-1, allogeneic cord blood regulatory T cells) are in early phase trials. Further translational studies to target leukemic stem cells, improvement in trial designs by incorporating control arm and survival endpoints, and patient-focused collaborations among all stakeholders could pave a way for future success in MF drug development.